ASXL2 Regulates Glucose, Lipid, and Skeletal Homeostasis - Takashi Izawa; Nidhi Rohatgi; Tomohiro Fukunaga; Qun-Tian Wang; Matthew J. Silva; Michael J. Gardner; Michael L. McDaniel; Nada A. Abumrad; Clay F. Semenkovich; Steven L. Teitelbaum; Wei Zou (Cell Reports, 2015)
ASXL2 is an ETP family protein that interacts with PPARγ. We find that ASXL2−/− mice are insulin resistant, lipodystrophic, and fail to respond to a high-fat diet. Consistent with genetic variation at the ASXL2 locus and human bone mineral density, ASXL2−/− mice are also severely osteopetrotic because of failed osteoclast differentiation attended by normal bone formation. ASXL2 regulates the osteoclast via two distinct signaling pathways. It induces osteoclast formation in a PPARγ/c-Fos-dependent manner and is required for RANK ligand- and thiazolidinedione-induced bone resorption independent of PGC-1β. ASXL2 also promotes osteoclast mitochondrial biogenesis in a process mediated by PGC-1β but independent of c-Fos. Thus, ASXL2 is a master regulator of skeletal, lipid, and glucose homeostasis.